The Influence of Service Quality, Hospital Reputation, and Promotion Strategies on Patient Loyalty - Andi Aulya Puji Tenriangka; Andi Thalia Resky Aulia; Febi Melindah MR; Innocentius Bernarto (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study explores the influence of service quality, hospital reputation, and promotion strategies on patient loyalty in private hospitals in Bone. This topic was chosen because patient loyalty is a key factor in the sustainability of health institutions. Qualitative studies explore patient experiences and management perspectives related to the relationship between these factors are still limited. This study used a descriptive qualitative approach with semi-structured interviews with patients, marketing managers, and medical personnel; service observation; as well as analysis of promotional documents. Thematic analysis of transcripts and observational data revealed three main themes: the dimensions of service quality (reliability, communication, responsiveness) that affect satisfaction; a reputation role built through professional credibility and patient testimonials; and the effectiveness of promotional strategies as determined by the consistency of the message and the credibility of the source. The findings show that the quality of service and reputation are the main determinants of patient return intentions and recommendations, while promotion serves to increase awareness but needs to be supported by service quality to maintain loyalty. These results confirm the importance of integrating service quality improvement, reputation management, and ethical promotional practices to increase patient loyalty and hospital sustainability.